2015
DOI: 10.1007/s00122-015-2495-z
|View full text |Cite
|
Sign up to set email alerts
|

Marker assisted separation of resistance genes Rph22 and Rym16 Hb from an associated yield penalty in a barley: Hordeum bulbosum introgression line

Abstract: The resistance genes Rph22 and Rym16 (Hb) transferred into barley from Hordeum bulbosum have been separated from a large yield penalty locus that was present in the original introgression line '182Q20'. The Hordeum bulbosum introgression line '182Q20' possesses resistance to barley leaf rust (Rph22) and Barley mild mosaic virus (Rym16 (Hb) ) located on chromosome 2HL. Unfortunately, this line also carries a considerable yield penalty compared with its barley genetic background 'Golden Promise'. Quantitative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…2HL. Recently, Johnston et al (2015) has demonstrated the usefulness of a similar approach using overlapping Hb segments to generate ILs with particular small introgression sizes.…”
Section: Strategy To Avoid Low Interspecific Recombinationmentioning
confidence: 99%
“…2HL. Recently, Johnston et al (2015) has demonstrated the usefulness of a similar approach using overlapping Hb segments to generate ILs with particular small introgression sizes.…”
Section: Strategy To Avoid Low Interspecific Recombinationmentioning
confidence: 99%
“…In addition to cloned eIF4E and PDIL5-1 , rym7 [ 26 ], Rym16 HB [ 27 , 28 ], Rym17 [ 29 ] and Rym14 HB [ 4 ] have been fine-mapped to a small region on chromosome 1H, 2H, 3H, and 6H, respectively. The remaining 10 BYMD-resistant genes rym8 [ 30 ], rym9 [ 31 ], rym12 [ 32 ], rym13 [ 33 ], rym18 [ 29 ], rym3 [ 34 ], Un-designated [ 35 ], rym15 [ 36 ], rym2 [ 32 ] and rym7t [ 37 ] have been preliminarily mapped.…”
Section: Backgroundsmentioning
confidence: 99%
“…However, this performance under stress conditions should not be at the cost of yield under control or non-submergence conditions, since flooding usually occur once in 2–5 years. Previous studies have reported contrasting results showing favorable, unfavorable or even neutral effects of different genes incorporated in various crop species 28 , 29 . However, replete knowledge on the influence of Sub1 QTL on yield and yield related parameters in farmers’ fields not affected by floods is incomplete.…”
Section: Introductionmentioning
confidence: 96%